Effects of Bioactive Packaging Films Incorporated with Bifidocin A on Microbial Reduction and Quality Parameters of Chill-Stored Spanish Mackerel (Scomberomorus niphonius) Fillets - Guorong Liu; Xue Li; Xu Hao; Chengtao Wang; Baoguo Sun (Journal of Food Quality)
To evaluate the potential of bifidocin A for preservation of fresh Spanish mackerel fillets, the bioactive packaging films incorporated with bifidocin A (1 × minimal inhibition concentration (MIC), 2 × MIC and 4 × MIC) were developed, and their effects on the microbiological and physicochemical properties and sensory profile of mackerel fillets at refrigerated storage were investigated. Results showed that the incorporation of bifidocin A in cellulosic matrix films did not affect the thickness and elongation of the films, but reduced slightly the tension strength. The films incorporated with 2 × MIC and 4 × MIC bifidocin A presented a broad spectrum of activity against most tested bacteria, including some fish-borne specific spoilage bacteria such as Pseudomonas fluorescens, Shewanella putrefaciens, Brochothrix thermosphacta, and Micrococcus luteus, and maintained their 100% activity for 28 days during storage at 4°C. The bioactive packaging films incorporated with bifidocin A could generally suppress the growth of microflora, especially Pseudomonas and Enterobacteriaceae, as well as substantially inhibit the accumulation of total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS) and hypoxanthine, during chilled mackerel fillets storage. Overall, from a microbiological and physicochemical point of view, a much more effective treatment was achieved with 4 × MIC bifidocin A, extending the shelf life to 12 days and maintaining the relatively low TVB-N value (≤13.2 mg/100 g), TBARS value (≤0.45 mg MDA/kg), and K-value (≤32.8%), as well as a relatively high sensory score (≥7.1) during the whole storage. Hence, the bioactive packaging films incorporated with bifidocin A could be a promising hurdle technology and alternative to conventional processes used for improving the safety and quality of chilled mackerel fillets.